Effect of plant density and tillage on the production of beans (Phaseolus vulgaris L) in two crop cycles in alley farming production system - Quintanilla Quintanilla, J.R. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 1995